Development of E-Learning with Web Enhanced Course Model in Arabic Language Learning at UIN Syarif Hidayatullah - Zainal Muttaqin; Yazid Hady; Toto Edidarmo (TARBIYA: Journal of Education in Muslim Society, 2021)
AbstractThe aim of this study was to develop the design of the e-learning concept through web-enhanced model for students at the Department of Arabic Education at UIN Syarif Hidayatullah Jakarta. Research and Development (R&D) by using a 4-D model. The 4-D development model consists of four main stages, namely: Define, Design, Develop and Disseminate. Data were collected through interview and distribution of questionnaire. After that, data analysis process was conducted in the form of both qualitative and quantitative data analysis. The results of the study showed that the development of e-Learning in Arabic learning gave students a new experience / nuance in learning Arabic for 63.5%. In terms of human resources, there is still an assumption that the conventional learning model through face-to-face is still an easy means and at the same time pays attention to the emotional bond between educators and students. This study concludes that the use of e-Learning media is still new to learning Arabic, and therefore, literacy in digital media needs to be developed to make them more accustomed to using it. Moreover, there are still many shortcomings and complaints by students in using e-Learning media in Arabic learning, and therefore, it required lecturers to be more intensive in guiding them.AbstrakPenelitian ini bertujuan untuk pengembangan desain konsep e-learning dengan Model Web Enhanced pembelajaran bahasa Arab pada generasi Z yaitu Mahasiswa pada Jurusan Pendidikan Bahasa Arab di UIN Syarif Hidayatullah Jakarta. Jenis penelitian yang digunakan yaitu dengan mengacu pada research and development (R&D) by using a 4-D model. Model pengembangan 4D terdiri atas 4 tahap utama yaitu: Define (Pendefinisian), Design (Perancangan), Develop (Pengembangan) dan Disseminate (Penyebaran). Dan teknik pengumpulan data yang diterapkan dengan wawancara dan kuesioner. Adapuun Analisis data yang diterapkan dalam penelitian ini adalah analisis data kualitatif dan analisis data kuantitatif. Hasil penelitian yang didapat bahwa pengembangan e-learning dalam pembelajaran bahasa arab memberikan mahasiswa pengalaman/nuansa baru dalam pembelajaran bahasa arab yakni sebesar 63.5%. Dari sisi sumber daya manusianya sendiri masih ada anggapan bahwa model pembelajaran konvensional melalui tatap muka masih menjadi sarana yang mudah dan sekaligus memperhatikan ikatan emosional antara pendidik dengan peserta didik. Kesimpulan pada penelitian ini adalah penggunaan media e-learning ini masih baru pada pembelajaran Bahasa Arab, tentunya literasi pada media digital perlu dikembangkan sehingga mahasiswa lebih terbiasa dalam menggunakannya. Masih banyak kekurangan dan keluhan oleh mahasiswa dalam menggunakan media e-learning dalam pembelajaran, sehingga mengharuskan dosen harus lebih intens lagi dalam membimbing mereka.